The maker revolution : building a future on creativity and innovation in an exponential world - Hatch, Mark R. (Wiley, 2018)
"Become a force for change through community, access, knowledge, and innovation The Maker Revolution is a guidebook to the new industrial revolution. Artisans, crafters, DIYers, and inventors around the globe are changing the way we change the world--are you ready to join the movement? This book shows you how to find your place in the revolution. You'll learn how the movement came about, and how Makers are already shifting paradigms and pushing the boundaries of innovation. You'll discover the people, organizations, and technologies that are catalyzing a re-thinking of industry, business, economic development and education, and you'll explore the ways in which specific types of participation could propel the movement toward greater access and inclusivity. You may even discover your own inner Maker, and decide to join the revolution. The world's greatest problems will only be solved by the creativity, ingenuity, and innovation of its inhabitants. The Maker Movement and the revolution it heralds holds that truth at its core, and strives to give everyone access to the knowledge, tools, experience, and community they need to change the world. This book takes you inside the movement, and helps you find your place. Understand the drivers, depths, and goals of the Maker Movement Explore the major trends and technologies that enable makers Learn how institutions can engage and participate in the Maker Revolution Find your inner revolutionary and become a part of the changing world The new revolution will not be televised--it will be something you hold in your hand, something you use every day, and the spirit of the community that created it. The Maker Revolution brings you into the fold to show you the power of breaking away from the status quo and will show you how you too can help change the world"--